Evolution of hierarchically formed petal-like 3 dimensional layer structures for SnS2 via ratio control of Sn/thiourea and their electrochemical charge storage behavior. Issue 15 (1st August 2021) - Kumar, Niraj; Mishra, Dhananjay; Kim, Seung Yeob; Yoo, Yongseok; Jin, Sung Hun
Abstract: Herein, the successful synthesis of tin sulfide compounds by a facile one-step solvothermal method is reported, and its evolution of hierarchically formed petal-like 3-dimensional layer structures for SnS2 via ratio control of Sn/thiourea(TU) is systematically investigated. With the increase of TU content, the two-dimensional layered structure is clearly changed from discrete to hierarchically dense nanostructure. Thus, among various conditions, SnS2 with 1:2 ratio (SNS12) shows superior electrochemical performance associated with its discrete nanostructure. In this study, sample SNS12 shows a high specific capacitance of 1403 F g -1 at 1 mVs -1, a high power density of 456.42 W h kg -1 at an energy density of 46.84 W kg -1 with the stable cyclic performance of 85.87% up to 5000 cycles. The enhanced electrochemical performances are attributed to its unique ultrathin petal discrete structure, which allows for fast ion/electron transfer, high active sites, short diffusion distance, and more electrolyte/electrode interface access. Moreover, a fabricated symmetric supercapacitor device has a high capacity to operate commercial LED, leading to the validation of its practical operation durability for synthesized material on a device-level application. This study suggests that favorably layered 3D SnS2 electrode materials and their controllable protocols via Sn/TU ratio modulation could be one of the beneficial direction for the envisioned energy storage applications. Graphical abstract: Image 1 Highlights: Facile one-step solvothermal method synthesis of tin sulfide compounds for supercapacitor application. 1:2 ratio-based ultrathin petal discrete layered structure gives remarkable cyclic and electrochemical characteristics. Important performance parameter of layered structure and petal thickness is optimized via thiourea ratio controlled growth. SNS12 layered structure exhibit high capacitance of 1403 F g -1 and excellent cyclic stability of 85.87% up to 5000 cycles.